Thermal dechlorination of PCB-209 over Ca species-doped Fe2O3. (February 2016) - Su, Guijin; Huang, Linyan; Shi, Ruifang; Liu, Yexuan; Lu, Huijie; Zhao, Yuyang; Yang, Fan; Gao, Lirong; Zheng, Minghui
Abstract: Degradation reaction of decachlorobiphenyl (PCB-209) was investigated over the synthesized Ca species-doped Fe2 O3 at 300 °C. The 1%Ca–Fe2 O3 exhibited the highest activity among the four catalysts prepared with the pseudo-first order reaction at k obs  = 0.103 min −1 . PCB-207, PCB-197, PCB-176, PCB-184, PCB-150, PCB-136, PCB-148, PCB-104, PCB-96, PCB-54, PCB-19, PCB-4 and PCB-1 were identified as the dominant isomers in their respective nonachlorobiphenyl (NonaCB) to monochlorobiphenyl (MonoCB) homologue groups. Analysis of the hydrodechlorination products indicated that dechlorination was much more favored on meta - and para -than on ortho -positions. The formation of significantly predominant NonaCB and octachlorobiphenyl (OctaCB) isomers was attributed to lower energy principles and to the 90° dihedral angles of two aromatic rings which prevented the hydrodechlorination at ortho -positions. When the number of chlorine atoms is not more than 7, the steric effect supports the formation of predominant PCB isomers having chlorines at four ortho -positions. During the dechlorination of tetrachlorobiphenyl (TetraCB) formed to generate monochlorobiphenyl (MonoCB) isomers, the chlorine atoms fully substituted at the ortho -positions have to be successively removed, with the first two dechlorinations preferentially occurring at the two different benzene rings. This is dissimilar to that of octachloronaphthalene (PCN-75) in which the hydrodechlorination reaction happened preferentially at ortho -position due to the existence of steric effects. The opposite roles of the steric effect in ortho -position between PCB-209 and PCN-75 might be due to the difference of the π-conjugated plane caused by the dihedral angle of 90° and 0° of the two aromatic rings. Highlights: 1% mol Ca species enhanced the activity of Fe2 O3 in the degradation of DecaCB. Dominant Nona-MonoCB isomers were determined during hydrodechlorination reaction. Thermodynamic and/or steric effects drive conversion. Steric effect prevented the hydrodechlorination at ortho-positions.